EKONOMI ZAKAT DAN REDISTRIBUSI KEKAYAAN: JALAN MENUJU KEADILAN SOSIAL ISLAM - Miftahurrahmat, Miftahurrahmat; Munzirin, Al (Mukhtasab: Journal of Economics and Islamic Business, 2025)
This article explores the role of zakat as a central instrument in the Islamic economic system, functioning as a means of wealth redistribution and achieving social justice. Zakat embodies not only spiritual obligations but also economic and social values that strengthen the welfare structure of the Muslim community. This study employs a qualitative approach using library research to analyze both classical and contemporary literature concerning the role of zakat in Islamic economics. The findings reveal that zakat significantly contributes to reducing social inequality, enhancing the welfare of the poor, and fostering social solidarity. The optimization of zakat requires professional, transparent, and digitally integrated management systems. Moreover, productive zakat can transform recipients (mustahik) into contributors (muzaki), promote economic independence, and support sustainable development. Integrating zakat into national fiscal policies also strengthens economic stability and advances the realization of Islamic social justice. Therefore, zakat should be regarded not merely as a religious obligation but as a strategic pillar of the Islamic economic framework that contributes to building a just, prosperous, and civilized society.